2014
DOI: 10.1186/bf03352243
|View full text |Cite
|
Sign up to set email alerts
|

A Coupled Map Lattice model for geomagnetic polarity reversals that exhibits realistic scaling

Abstract: Seki and Ito (1993) showed that the geomagnetic polarity reversals had a power-law distribution and presented a simple model in which the geodynamo was assumed to be a system of magnetic spins in a critical phase-transition state. We present an improved, more realistic model, and obtain a power exponent in agreement with the observed value, which is about −1.5. The revised model is a Coupled Map Lattice (CML). A CML is a dynamical system with discrete time and space, but continuous state. In the present model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…A similar physical model, the Rikitake disk dynamo (Rikitake 1958, Seki & Ito 1999 has been favored to explain the statistical distribution of Earth's magnetic field reversals. Under certain parameter ranges, this system of equations has been shown to undergo "Lorenz-type" nonlinear evolution, with projections of the flow onto two-dimensional phase space planes showing two regions organizing the flow (McMillen 1999).…”
Section: Disk Magnetic Fieldsmentioning
confidence: 99%
“…A similar physical model, the Rikitake disk dynamo (Rikitake 1958, Seki & Ito 1999 has been favored to explain the statistical distribution of Earth's magnetic field reversals. Under certain parameter ranges, this system of equations has been shown to undergo "Lorenz-type" nonlinear evolution, with projections of the flow onto two-dimensional phase space planes showing two regions organizing the flow (McMillen 1999).…”
Section: Disk Magnetic Fieldsmentioning
confidence: 99%
“…[39] Hypothetically, the random walk description could be linked to local and statistically independent dynamo processes in the Earth's outer core, similar to those envisaged by Mazaud and Laj [1989] or Seki and Ito [1999]. If each process creates a chaotically switching dipole field, essentially aligned with the rotation axis, either parallel or antiparallel, then their sum undergoes a one-dimensional random walk.…”
Section: Discussionmentioning
confidence: 99%
“…For α ≤ 2 the average polarity duration for (1) becomes infinite for observation times T → ∞ , leading to the appearance of strong fluctuations in t , which can be mistaken for nonstationary behavior. Accordingly, the observed superchrons—instead of being outliers—would be an intrinsic feature of the distribution [ Seki and Ito , 1999; Pelletier , 1999; Jonkers , 2007]. The idea that the appearance of superchrons are a consequence of the nonlinear nature of the geodynamo was also defended by Hulot and Gallet [2003] on the grounds of their analysis of the GPTS and by Aubert et al [2009] who concluded that results of their numerical simulations of the geodynamo work “support the idea of superchrons being integral to the variety of timescales spontaneously produced by the dynamo.”…”
Section: Introductionmentioning
confidence: 99%
“…By numerical simulation, they found that intervals of polarity reversals in the model follow a power law at a critical state. They also improved their model (Seki and Ito, 1999) to make it more realistic and to obtain a power exponent closer to the observed value. The revised model is a coupled map lattice where the elements themselves evolve and reverse polarity autonomously according to the Lorentz map obtained from Rikitake dynamo dynamics.…”
Section: Introductionmentioning
confidence: 99%